Sarajevo Related Video Recordings
The collection covers the siege of Sarajevo during the Bosnian War, when Serb forces and the Yugoslav People’s Army circled and blockaded the city for almost 4 years, from April 1992 to February 1996. It contains 48 tapes with edited and unedited footage, including raw and background footage, documentaries, event recordings, television programs and news reports. The large majority of the collection consists of short films and raw material produced by SaGA (Sarajevo Group of Authors), a group of over 30 multi-ethnic professionals and filmmakers from Sarajevo which documented the Bosnian war as it was unfolding. SaGA’s teams particularly covered the first 2 years of the war when the siege was at its height and grave abuses were committed. The highlights of the collection are: “Sarajevo: A Street Under Siege,” a 2-minute film broadcast every night on BBC, bringing a day-by-day account of how the siege was affecting a group of ordinary citizens, and “Confessions of a Monster” which features a raw interview with the first person to be charged with the crime of genocide since World War II. Overall, the collection offers first-hand material testifying to the massacres in Sarajevo, the damage caused by war, and the grave human rights violations. Accruals not expected